(Re)Situating Cognition: Expanding Sociocultural Perspectives in Adult Education - Kim L. Niewolny; Arthur L. Wilson (Adult Education Research Conference, 2006)
We review key sociocultural perspectives of learning and cognition to begin to “make good” on the promise of situated cognition in adult education by incorporating its too-often ignored political analysis.
Keywords: Political analysis; learning and cognition; adult education